2022
DOI: 10.1101/2022.05.08.491072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the limits of fitting complex models of population history to genetic data

Abstract: Our understanding of human population history in deep time has been assisted by fitting “admixture graphs” to data: models that specify the ordering of population splits and mixtures which is the only information needed to capture the patterns of allele frequency correlation among populations. Not needing to specify population size changes, split times, or whether admixture events were sudden or drawn out simplifies the space of models that need to be searched. However, the space of possible admixture graphs r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(130 citation statements)
references
References 72 publications
1
129
0
Order By: Relevance
“…A question arises: is it justified to put a lot of weight on a particular graph and derive historical interpretations of its topology if hundreds of diverse topologies fit the data equally well? This is a key point discussed by Maier et al 17 when revisiting admixture graphs from eight published studies. For instance, it was found that there are at least several models fitting the data significantly better than the admixture graph for East Asians used to support a key conclusion by Wang et al 13 , and the alternative models do not support the conclusion.…”
Section: Admixture Graph Models Of Genetic Historymentioning
confidence: 92%
See 3 more Smart Citations
“…A question arises: is it justified to put a lot of weight on a particular graph and derive historical interpretations of its topology if hundreds of diverse topologies fit the data equally well? This is a key point discussed by Maier et al 17 when revisiting admixture graphs from eight published studies. For instance, it was found that there are at least several models fitting the data significantly better than the admixture graph for East Asians used to support a key conclusion by Wang et al 13 , and the alternative models do not support the conclusion.…”
Section: Admixture Graph Models Of Genetic Historymentioning
confidence: 92%
“…We note that the same constraints on the graph topology were applied as in the original study: French or Mbuti were assigned as an outgroup. Even a shallow exploration of both graph spaces found hundreds of models that fit the data as good as the published ones, and deeper exploration (performing more findGraphs runs and/or extracting more graphs from each run) is guaranteed to deliver further and further models of this kind 17 .…”
Section: Admixture Graph Models Of Genetic Historymentioning
confidence: 99%
See 2 more Smart Citations
“…We first performed pairwise qpWave modeling using the qpwave function from the R package “ ADMIXTOOLS2 ” 42 . We considered a pair composed of the target individual AB M-40/I1680 from Cambodia and one of the 13 reference populations as “left populations”.…”
Section: Methodsmentioning
confidence: 99%